Tracing the Signal from Teachers to Students: How Teachers' Motivational Beliefs Longitudinally Relate to Student Interest through Student-Reported Teaching Practices - Lazarides, Rebecca; Schiefele, Ulrich; Hettinger, Katharina; Frommelt, Marthe C (Journal of educational psychology, 2023)
Theoretical models have suggested that teachers' motivational beliefs relate to various student academic outcomes through particular teaching practices, and that teachers' motivational beliefs and teaching practices are reciprocally interrelated. However, these relations have rarely been tested in longitudinal work. We extend previous research by (a) examining whether mathematics teachers' self-efficacy and interest longitudinally relate to student mathematics interest through student-reported teaching practices (classroom management, socioemotional support, cognitive activation) and by (b) testing reciprocal relations between teachers' motivational beliefs and student-reported teaching practices. Participants were 50 mathematics teachers (66.0% female) and their n = 959 students (47.9% girls; Mage: 14.20, SD = 0.62). Longitudinal multilevel models revealed different paths from teachers' motivational beliefs to students' interest: a "behavioral management path" from teacher self-efficacy for classroom management (Time 1) to student interest (Time 3) through student-perceived classroom management (Time 2), an "affective support path" from teacher self-efficacy for engagement (Time 1) to student interest (Time 3) through socioemotional support (Time 2), and a "cognitive instruction path" from teacher educational interest (Time 1) to student interest (Time 3) through cognitive activation (Time 2). We did not find reciprocal relations between teachers' motivational beliefs and their teaching practices. Our findings suggest that different dimensions of teachers' motivational beliefs are associated with different teaching practices, which in turn relate to student motivation.